The ‘Old Testament’ as the origin of the patriarchy - Hanna Liljefors (Nordisk Judaistik, 2023)
This article explores and compares two similar debates in Germany and Sweden during the 1980s, in which feminists blamed the Hebrew Bible, or ‘Old Testament’, for being the origin of the patriarchy. In Germany, the psychologist and pedagogue Gerda Weiler articulated the discourse in several writings, which led to a scholarly debate on anti-Jewish tendencies within Christian feminist theology. In Sweden, the debate mainly became a media event, initiated by the author Birgitta Onsell. Instead of criticising the discourse, as in the German debate, other actors reinforced it, for example by highlighting Jesus as a feminist and a contrast to the Old Testament religion. The article further examines ideological consequences of the discourse, including the interdiscursive link to the notion of Judaism as responsible for the patriarchal moral that enabled the Holocaust, also expressed in the public sphere in Germany and Sweden.